Alguém me ajuda na 5?
obs: deixe a conta
Anexos:
Soluções para a tarefa
Respondido por
1
= ( a³ - 3a²b + 3ab² + b³ ) - a³ + b³ + 4ab . ( a - b)
= a³ - 3a²b + 3ab² + b³ - a³ + b³ + 4a²b - 4ab²
=0 - 3a²b + 3ab² + 2b³ + 4a²b - 4ab²
= a²b - ab² + 2b³
Obs: Acho que é assim
= a³ - 3a²b + 3ab² + b³ - a³ + b³ + 4a²b - 4ab²
=0 - 3a²b + 3ab² + 2b³ + 4a²b - 4ab²
= a²b - ab² + 2b³
Obs: Acho que é assim
ray214:
obg
Perguntas interessantes
Geografia,
8 meses atrás
Informática,
8 meses atrás
Geografia,
8 meses atrás
Matemática,
1 ano atrás
Administração,
1 ano atrás
Física,
1 ano atrás
Biologia,
1 ano atrás